2005
DOI: 10.2169/internalmedicine.44.1157
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hospital-acquired Bacteremia

Abstract: Objective Bacteremia is one of the most serious health problems associated with high morbidity and mortality. The aim of this study was to identify risk factors for bacteremia in daily medical care to facilitate rapid and accurate clinical decisions about treatment.Patients and Methods We studied 306 inpatients retrospectively. Age, peripheral neutrophil count, C-reactive protein (CRP), platelets, serum total cholesterol, total protein, albumin and cholinesterase were compared in patients with positive-and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 18 publications
2
17
1
2
Order By: Relevance
“…Other invasive procedures such as urinary catheterization and endotracheal intubation might also be assumed as potential source of nosocomial infection [32,33]. However, in our patients these had no significant influence on the infection of necrotic tissue with resistant strands of bacteria.…”
Section: Discussionmentioning
confidence: 64%
“…Other invasive procedures such as urinary catheterization and endotracheal intubation might also be assumed as potential source of nosocomial infection [32,33]. However, in our patients these had no significant influence on the infection of necrotic tissue with resistant strands of bacteria.…”
Section: Discussionmentioning
confidence: 64%
“…A presença de 15 ou mais UFC em culturas de pontas de cateteres tem sido associada a uma incidência de 16% de bacteremia. Os CVC contribuem com 75 a 90% de todas as infecções da corrente sangüínea, relacionadas a cateteres (EGGIMANN; SAX; PITTET, 2004;YOSHIDA et al, 2005 O processo infeccioso depende da eficiência com que o microrganismo consegue colonizar a pele, causar alterações patológicas no sítio de inserção e disseminarse para a corrente sanguínea, ou a uma nova área. Jarvis (1996) considera que ocorre aumento do risco de infecção em pacientes imunocomprometidos por estados clínicos graves, em portadores de doenças de base e em extremos de idade.…”
Section: Resultsunclassified
“…A previous study suggested that neutropenia is a factor that contributes to hospital-acquired bacteremia (Yoshida et al 2005). However, there have been no reports describing the relationship between leucopenia and the mortality of MRSA bacteremia.…”
Section: Discussionmentioning
confidence: 99%